Proyecto de elaboración y comercialización de snacks a partir de la corteza de la tagua en la ciudad de Guayaquil - Ayerve Bermúdez, Diana Estefanía (2009)
This Project has been made in order to simulate to the best use of a natural product as it is the ivory palm whose scientific name is MICORCARPHAS RHITELEPHAS